Influence of flavonoids’ lipophilicity on platelet aggregation - Babić Ivana; Bojić Mirza; Maleš Željan; Zadro Renata; Gojčeta Koraljka; Duka Ivan; Rimac Hrvoje; Jukić Irena (Acta Pharmaceutica)
Flavonoids are natural polyphenolic compounds present in a wide spectrum of plants that have a beneficial effect on human health. In the context of cardiovascular diseases related to plaque and thrombus formation, flavonoids exhibit an anti-aggregatory effect. Previously, it has been reported that all tested flavonoids exhibit an antiaggregatory effect on platelet aggregation when measured by impedance aggregometry on whole blood, in the test of aggregation induced by adenosine diphosphate (ADP). As not all flavonoids have the same targets within signaling pathways, an assumption of a common non-specific mechanism related to lipophilicity is to be considered. To test this hypothesis, reverse-phase thin layer chromatography was used to assess the lipophilicity of flavonoids; impedance aggregometry was used for testing of platelet aggregation and flow cytometry to monitor the influence of flavonoids on platelet activation. Lipophilicity analysis showed a highly negative correlation of logP and MINaAC for groups of flavones and flavanones. As determined by flow cytometry, the exposition of receptors necessary for the promotion of platelet activation and primary clot formation was diminished, i.e., lowered expression of the activated form of integrin αIIbβ3 was observed in the presence of flavanone. Platelet membrane stabilization by flavonoids as a mechanism of antiaggregatory effect has been supported by impedance aggregometry experiments when specific inhibitors of platelet aggregation signaling pathways (U73122, indomethacin, verapamil) were used in the presence of a weak (ADP) and a strong (TRAP-6) agonist of aggregation. While individual flavonoids can have specific targets within aggregation signaling pathways, all flavonoids share a common non-specific mechanism of platelet aggregation inhibition related to their lipophilicity and membrane stabilization that, to some extent, contributes to their antiaggregatory effect.